Specific Features of Sound Directing in Karakalpak National Cinema - Abdreymov Manas Bekpolatovich (Researchparks Publishing, 2021)
This article examines the current state and development trends of the voice director in Karakalpak cinema on an analytical basis. Theoretical and practical research has been conducted in this area. At the same time, the peculiarities of sound directing in Karakalpak cinema were considered.